DISTRIBUTION OF SEAGRASSES IN INNER AMBON BAY - Andri Irawan; Noorsalam R. Nganro (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
ABSTRACTExcessive sedimentation in Inner Ambon Bay (IAB) is alleged to cause the degradation of seagrass ve-getation in the area. To get a clearer picture about the matter, we conducted a field study in October 2010 - January 2011 to describe the distribution and density of seagrass at several locations in IAB with different conditions of sedimentation levels. Data were collected using transects perpendicular to the coastline along the seagrass vegetation. The results showed that there were six species of seagrass which were spreaded unevenly. At the locations with high sedimentation, we found the formation of monospecies seagrass vegetation. Conversely, at the locations with low sedimentation, we found the formation of multispecies seagrass vegetation. The distribution and abundance of each species was related to the differences of seagrasses ability to grow in a certain environment and the compe-titiveness among them. Keywords: sedimentation, distribution, seagrass, Inner Ambon Bay